The displaced : refugee writers on refugee lives - Nguyen, Viet Thanh, 1971-; Azam, Joseph; Bezmozgis, David, 1973-; Bhutto, Fatima, 1982-; Bui, Thi; Dorfman, Ariel; Golinkin, Lev; Grande, Reyna; Hadero, Meron; Hemon, Aleksandar, 1964-; Kertes, Joseph, 1951- (Abrams Press, 2018)
Pulitzer Prize-winning author Viet Thanh Nguyen, himself a refugee, brings together a host of prominent refugee writers from around the world to explore and illuminate their experiences. Poignant and insightful, this collection of essays reveals moments of uncertainty, resilience int he face of trauma, and a reimagining of identity. The Displaced is a powerful look at what it means to be forced to leave home and find a place of refuge. -- Adapted from book jacket.